A real‐world observational cohort of patients with primary biliary cholangitis: TARGET‐primary biliary cholangitis study design and rationale. Issue 5 (23rd March 2018) - Levy, Cynthia; Bowlus, Christopher L.; Carey, Elizabeth; Crawford, Julie M.; Deane, Karen; Mayo, Marlyn J.; Kim, W. Ray; Fried, Michael W.
Abstract : TARGET‐PBC is a longitudinal observational study conducted in both academic and community sites to create a real‐world view of the natural history and clinical management of PBC in patients who are diagnosed and treated in this setting. Importantly, data generated from this study will address gaps in our knowledge of the clinical effectiveness of PBC‐related interventions and provide valuable post‐marketing surveillance of new PBC therapies. Abstract : Primary biliary cholangitis (PBC) is a rare chronic cholestatic liver disease that may progress to biliary cirrhosis if left untreated. The first‐line therapy for PBC is ursodeoxycholic acid (UDCA). Unfortunately, 1 of 3 patients does not respond to UDCA. These patients are at risk for developing clinical events, including cirrhosis, complications of portal hypertension, hepatocellular carcinoma, liver transplant, or death. Recently, the U.S. Food and Drug Administration approved obeticholic acid to be used in certain patients with PBC. Off‐label therapies are also used, and several other therapies are currently under evaluation. Real‐world effectiveness of newly approved and off‐label therapies remains unknown. TARGET‐PBC is a 5‐year, longitudinal, observational study of patients with PBC that will evaluate the effectiveness of clinical practice interventions and provide practical information unobtainable in registration trials. Enrollment will take place at both academic and community sites. In addition to consenting to medical records review, participants will be asked to provide an annual blood sample and complete patient reported outcome surveys at predetermined intervals. Any available liver biopsies will be digitally preserved. Conclusion: Key study outcomes will be the evaluation of the safety and effectiveness of PBC interventions and the assessment of disease progression under real‐world conditions. ( Hepatology Communications 2018;2:484‐491)